The Clinical Outcome of Elevated Peri-Operative Lactate Levels in Patients Undergoing Craniotomy - Ahmed Amer Abdulhussein; Ahmed Bassam Rasheed; Zahraa Kamil Yousif; Marwah Mohammed Qasim (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2026)
Elevated perioperative serum lactate is a common finding during craniotomy, but its clinical significance and origin—whether reflecting systemic hypo perfusion or localized cerebral metabolic shifts—remain unclear. This study aimed to prospectively evaluate the association between intraoperative hyperlactatemia and postoperative outcomes in elective craniotomy patients. In this prospective study, 50 adult patients undergoing elective craniotomy for brain tumors or lesions were enrolled. Arterial blood gas analyses, including serum lactate measurements, were performed preoperatively, immediately postoperatively, and at 24 hours. Patients were stratified into High-Lactate (HL, ≥2 mmol/L) and Normal-Lactate (NL, <2 mmol/L) groups based on immediate postoperative levels. Primary outcomes included new postoperative neurological deficits and hospital length of stay (LOS). Secondary outcomes included systemic complications (renal failure, myocardial infarction, 30-day mortality). Data were analyzed using comparative statistics and logistic regression. Elevated immediate postoperative lactate (≥2 mmol/L) was observed in 30% (15/50) of patients. There was no statistically significant difference in the incidence of new neurological deficits between the HL (38.5%) and NL (27.3%) groups (p=0.31). Similarly, no cases of mortality, renal failure, or myocardial infarction occurred within 30 days. However, median hospital LOS was significantly longer in the HL group (6.5 days) compared to the NL group (3 days) (p=0.003). Regression analysis confirmed elevated intraoperative lactate as an independent predictor of prolonged hospitalization (p=0.036), but not of new neurological deficits. Infratentorial lesion location was associated with a higher odds of developing a new neurological deficit (OR=5.5, p=0.027). In patients undergoing elective craniotomy, isolated postoperative hyperlactatemia is not an independent predictor of new neurological deficits or major systemic complications. Its primary clinical correlate is a significantly extended hospital stay, suggesting an impact on resource utilization and recovery pace. These findings challenge the routine use of serum lactate as a specific alarm biomarker for neurologic injury in this context and highlight the need for investigation into more direct cerebral metabolic markers..